Overview of Acute Respiratory Infection Services during the COVID-19 Pandemic at Kupang Kota Health Center - Cathlyn Ivanna Salmon; Deviarbi Sakke Tira; Helga J. N. Ndun (Universitas Nusa Cendana, 2023)
The COVID-19 pandemic has an impact on sectors of life, particularly at the Public Health Center's health services. During the pandemic the COVID-19 pandemic, the health services at the Public Health Center experienced a transformation, with the flow of Acute Respiratory Infection (ARI) disease services being carried out by the necessary health standards. The goal of the study was to learn more about ARI disease services at the Kupang Kota Health Center before and during the COVID-19. This study used a qualitative research method, namely in-depth interviews with 15 informants. Data analysis used an interactive model, namely data reduction, data presentation, and conclusion drawing. The results showed that there were differences in ARI disease services before the COVID-19 pandemic and during the COVID-19 pandemic, both in terms of changing service flow because before carrying out services, patients had to do an antigen swab first, then if the results were negative, they would be served by officers Public Health Center, besides that there are several programs that have been postponed, such as integrated health care center, home visits. Counseling activities are carryout with a mobile health center using ambulances. The COVID-19 pandemic has caused a double workload for health workers at the Public Health Center, causing overlapping work. The solution is to have good communication and find a solution with the director of a Public Health Center. The conclusion of health services carryout before and during the COVID-19 pandemic has been running according to the applicable SOP.